2015
DOI: 10.1371/journal.pone.0127832
|View full text |Cite
|
Sign up to set email alerts
|

Critical Appraisal of Bivalirudin versus Heparin for Percutaneous Coronary Intervention: A Meta-Analysis of Randomized Trials

Abstract: Percutaneous coronary intervention with bivalirudin plus bail-out glycoprotein IIb/IIIa inhibitors has been shown to be as effective as unfractionated heparin plus routine glycoprotein IIb/IIIa inhibitors in preventing cardiac ischemic events, but with a lower bleeding risk. It is unknown whether bivalirudin would have the same beneficial effects if compared with heparin when the use of glycoprotein IIb/IIIa inhibitors was similar between treatment arms. We searched the MEDLINE, Web of Science, and Cochrane da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 56 publications
2
6
0
Order By: Relevance
“…The benefit was also noted only with higher doses of unfractionated heparin only, when the influence of glycoprotein IIb/IIIa inhibitors was balanced in both arms. Such results are similar to previous studies that explored the effect of bivalirudin versus unfractionated heparin on major bleeding, when the analysis was limited only to trials reporting balanced glycoprotein IIb/IIIa inhibitors use in both groups [5].…”
supporting
confidence: 88%
“…The benefit was also noted only with higher doses of unfractionated heparin only, when the influence of glycoprotein IIb/IIIa inhibitors was balanced in both arms. Such results are similar to previous studies that explored the effect of bivalirudin versus unfractionated heparin on major bleeding, when the analysis was limited only to trials reporting balanced glycoprotein IIb/IIIa inhibitors use in both groups [5].…”
supporting
confidence: 88%
“…We agree with the authors' postulate that reduction in bleeding may well explain the differences in mortality and major adverse clinical events observed because excess bleeding has consistently been demonstrated to increase mortality hazard in other data sets. [8][9][10][11] In this analysis, the addition of GPI was infrequent and did not affect the overall study outcome, further strengthening the hypothesis that bivalirudin reduces significant bleeding in PVI. It is worth noting that, although the arterial access site was not evaluated in this study, the vast majority of PVI procedures involving lower extremity PAD are performed via transfemoral access.…”
Section: See Article By Kimmelstiel Et Alsupporting
confidence: 62%
“…On the contrary, the recently published HEAT-PPCI (How Effective are Antithrombotic Therapies in Primary PCI) trial [26] reported that bivalirudin compared with heparin alone resulted in a significantly higher rate of major adverse ischemic events with no decrease in bleeding complications. The diverging results among RCTs demonstrated that concomitant administration of a GPI with heparin might influence the benefit of bivalirudin [27]. Whether bivalirudin decreased the risk of bleeding regard less of routine GPI use remains unknow.…”
Section: Discussionmentioning
confidence: 99%